1999
DOI: 10.1016/s0194-5998(99)70286-x
|View full text |Cite
|
Sign up to set email alerts
|

Current Status of Electronystagmography Testing

Abstract: ENG testing, whether computerized or not, remains the most useful means of assessing the vestibular system. The caloric test provides invaluable site-of-lesion information that objectively documents a peripheral vestibular lesion. Double (bithermal) caloric irrigation of each ear provides a more thorough and wider range test of inner ear function than a single caloric irrigation because the vestibular system is both excited and inhibited, causing responses in opposite directions, which are important in evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
0
9

Year Published

2000
2000
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(44 citation statements)
references
References 26 publications
2
33
0
9
Order By: Relevance
“…This feature is a "must-have feature" in this type of questionnaire [5,[33][34][35] . Demographic features, familial MD history, accompanying other systemic chronic disease history, and bilaterality of the disease findings were similar to those of other studies [36][37][38][39][40][41] . It has been reported that the emotional stress is the most powerful attack indicator [31,[41][42][43][44] .…”
Section: Discussionsupporting
confidence: 87%
“…This feature is a "must-have feature" in this type of questionnaire [5,[33][34][35] . Demographic features, familial MD history, accompanying other systemic chronic disease history, and bilaterality of the disease findings were similar to those of other studies [36][37][38][39][40][41] . It has been reported that the emotional stress is the most powerful attack indicator [31,[41][42][43][44] .…”
Section: Discussionsupporting
confidence: 87%
“…The lateral canal involvement was characterized by horizontal positional nystagmus. The most intense downwards geotropic nystagmus with the right ear indicated canalolithiasis on the right side; the most intense downwards geotropic nystagmus with the left ear indicated left lateral canal canalolithiasis; the most intense downwards ageotropic nystagmus with the right ear indicated left lateral canal cupulolithiasis; the most intense downwards ageotropic left year nystagmus indicated right lateral canal cupulolythiasis 10,19 . The patients with vertical canal involvement were treated by means of the Epley maneuver 14 and those with lateral canal involvement were treated by the LempertWilck maneuver 16 .…”
Section: Methodsmentioning
confidence: 95%
“…The anterior canal involvement was characterized by downwards and rotational vertical positional nystagmus (counterclockwise in the right labyrinth and clockwise in the left one). In vertical canal involvement, canalolithiasis was characterized by nystagmus lasting up to one minute and cupulolithiasis, by nystagmus lasting more than one minute 10,19 . The lateral canal involvement was characterized by horizontal positional nystagmus.…”
Section: Methodsmentioning
confidence: 99%
“…Because this technique directly compares the vestibular function on the right and left sides, caloric testing is highly reliable in detecting unilateral peripheral vestibular loss. 2,3,23,25,26 Each laboratory must determine its own normal range; however, in most testing centers a caloric paresis of greater than 22 to 25% indicates unilateral peripheral vestibular loss. Directional preponderance indicates nystagmus greater in one direction than in the other during caloric testing.…”
Section: Quantitative Vestibular Testing Eye Movement Recordingsmentioning
confidence: 99%
“…Caloric testing can result in artifactually reduced vestibular responses due to inadequate irrigation. 21,26,29 Rotational chair testing is also helpful in monitoring vestibular function when ototoxic medications such as gentamicin and cisplatin are administered, 28 in those with gait disequilibrium, 30 and in testing infants and young children, as will be discussed later. Knowing the degree of vestibular loss may also be useful in deciding whether a patient's balance rehabilitation should emphasize exercises that enhance residual vestibular function or those that retrain the individual to rely more on somatosensory and visual cues.…”
mentioning
confidence: 99%